2022
DOI: 10.1038/s41385-022-00498-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbial regulation of intestinal motility provides resistance against helminth infection

Abstract: Soil-transmitted helminths cause widespread disease, infecting ~1.5 billion people living within poverty-stricken regions of tropical and subtropical countries. As adult worms inhabit the intestine alongside bacterial communities, we determined whether the bacterial microbiota impacted on host resistance against intestinal helminth infection. We infected germ-free, antibiotic-treated and specific pathogen-free mice, with the intestinal helminth Heligmosomoides polygyrus bakeri. Mice harboured increased parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 66 publications
1
34
1
Order By: Relevance
“…Indirectly, helminth infection may alter the bacterial microbiome through an influence on immune homeostasis of the host, whether by altering inflammatory modulation, mucus production or antimicrobial peptide production (Ling et al, 2020; Reynolds et al, 2015). Alternatively, bacterial microbiome composition can alter parasite colonization success, replication and virulence through variation in the physical gut landscape (Leung et al, 2018; Moyat et al, 2022), suggesting that the establishment of strongylid communities may vary dependent on the bacterial microbiome. It is also possible, but unlikely, that observed covariations do not reflect interactions between strongylid nematodes and the bacterial microbiome but in fact echo specific bacterial and strongylid taxa showing harmonized responses to extraneous environmental variables (Reynolds et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirectly, helminth infection may alter the bacterial microbiome through an influence on immune homeostasis of the host, whether by altering inflammatory modulation, mucus production or antimicrobial peptide production (Ling et al, 2020; Reynolds et al, 2015). Alternatively, bacterial microbiome composition can alter parasite colonization success, replication and virulence through variation in the physical gut landscape (Leung et al, 2018; Moyat et al, 2022), suggesting that the establishment of strongylid communities may vary dependent on the bacterial microbiome. It is also possible, but unlikely, that observed covariations do not reflect interactions between strongylid nematodes and the bacterial microbiome but in fact echo specific bacterial and strongylid taxa showing harmonized responses to extraneous environmental variables (Reynolds et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, bacterial microbiome composition can alter parasite colonization success, replication and virulence through variation in the physical gut landscape (Leung et al, 2018;Moyat et al, 2022),…”
Section: Strongylid and Gut Bacterial Microbiome Covariationmentioning
confidence: 99%
“…A plethora of studies published over the last decade has pointed toward the occurrence of a complex network of interactions between GI helminths of humans and animals and the resident gut microbiota [ 38 44 ]; nevertheless, in spite of this evidence, the exact mechanisms underpinning such interactions have remained largely elusive [ 15 , 45 , 46 ]. In this study, we demonstrated that ESPs from T. circumcincta , a globally distributed GI nematode of small ruminants, exert antimicrobial activity in in vitro bacterial growth assays, and identified and characterised several proteins with putative antimicrobial activity that represent key targets of follow-up mechanistic studies of parasite-microbiota relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, it is mechanistically unclear how microbiome changes can influence susceptibility and pathogenesis of disease during helminth infection, although studies have shown that helminth infection can influence the microbiome composition and diversity in the host recently reviewed here (159). A recent study by Moyat et al, 2022 using germ-free, antibiotic-treated, and specific pathogen-free mice clearly demonstrated that the intestinal bacteria composition can have an impact on host resistance to intestinal helminth H. polygyrus (165). Depletion of a complex microbiota through long termtreatment with antibiotics or in germ free mice resulted in more susceptibility to worm infection via a mechanism that is dependent on intestinal acetylcholine, a neurotransmitter, necessary for intestinal motility (165).…”
Section: The Microbiome As a Major Environmental Variablementioning
confidence: 99%